The protective effect of resveratrol against risperidone-induced brain damage and metabolic side effects - Korkmaz, Deniz Tastemir; Bilgic, Sedat; Azirak, Sebile; Guvenc, Ayse Nilay; Kocaman, Nevin; Ozer, Mehmet Kaya (Cukurova Univ, Fac Medicine, 2018)
Purpose: The aim of this study was to investigate the protective effect of resveratrol (RSV) against risperidone (RIS) on weight gain/loss via of the expression of some various neurotransmitter receptors. Materials and Methods: Thirty five female Spraque-Dawley rats were divided into 5 groups (n=7): Control, RIS, RIS+RSV-1, RIS+RSV-2, RIS+RSV-3. Rats were treated orally with RIS (2 mg/kg/day) and RSV (20, 40 and 80 mg/kg/day) for 14 days. On treatment day 15, blood and brain tissues were removed for analysis. Results: The reduced neuropeptide Y1 expression levels in the RSV groups correlated with the RSV-induced weight loss. The Dopamine D1 receptor and seratonin 5-HT2c expression levels decreased significantly with RSV treatment. In addition, the RSV increased the glucose, triiodothyronine, tetraiodothyronine, and total antioxidant status, and decreased the cholesterol, triglyceride, high density lipoproteins, low density lipoproteins, thyroid-stimulating hormone, oxidative stress index, and total oxidant status levels significantly. Conclusion: The daily treatment with RSV increased the antioxidant capacity, protected the apoptotic cell injury, and the possibility of death. RSV could be an effective course of therapy to enhance therapeutic efficacy.
Keywords: Risperidone; resveratrol; weight gain/loss; dopamine D1 receptor